2021
DOI: 10.1371/journal.pone.0247186
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the effective reproduction number of COVID-19 through mobility and enterprise statistics: Evidence from the first wave in Japan

Abstract: This study uses mobility statistics combined with business census data for the eight Japanese prefectures with the highest coronavirus disease-2019 (COVID-19) infection rates to study the effect of mobility reductions on the effective reproduction number (i.e., the average number of secondary cases caused by one infected person). Mobility statistics are a relatively new data source created by compiling smartphone location data; they can be effectively used for understanding pandemics if integrated with epidemi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…Nagata et al, who tracked human mobility in Tokyo, Osaka, and Aichi Prefectures using smartphone data, pointed out that the reduction in human mobility started before the first declaration of the state of emergency, and that the degree of reduction varied from place to place [ 21 ]. Furthermore, Kajitani et al found that a 20–35% reduction in mobility may have been necessary to hold back the pandemic (i.e., to reduce the effective reproduction number to one or less) in the situation during the first wave of the pandemic in the business and commercial districts of nine prefectures including Tokyo [ 22 ]. These studies did not identify age-specific human mobility patterns as an analytical limitation, but we were able to show that the degrees of mobility reduction as well as the trend patterns after the emergency declarations varied among different age groups, and further varied at the small area level.…”
Section: Discussionmentioning
confidence: 99%
“…Nagata et al, who tracked human mobility in Tokyo, Osaka, and Aichi Prefectures using smartphone data, pointed out that the reduction in human mobility started before the first declaration of the state of emergency, and that the degree of reduction varied from place to place [ 21 ]. Furthermore, Kajitani et al found that a 20–35% reduction in mobility may have been necessary to hold back the pandemic (i.e., to reduce the effective reproduction number to one or less) in the situation during the first wave of the pandemic in the business and commercial districts of nine prefectures including Tokyo [ 22 ]. These studies did not identify age-specific human mobility patterns as an analytical limitation, but we were able to show that the degrees of mobility reduction as well as the trend patterns after the emergency declarations varied among different age groups, and further varied at the small area level.…”
Section: Discussionmentioning
confidence: 99%
“…Since the inception of the COVID-19 pandemic, much of the literature on epidemiological modeling and public-health messages alike have scrutinized different nonpharmaceutical interventions in relation with their impact on R , the effective reproduction number (Di Domenico et al, 2020; Kajitani and Hatayama, 2020). We estimate our simulations’ R value after t = 7 days (since t 0 ) from the corresponding exponential growth rate λ by applying Eq 1, following the Wallinga and Lipsitch (2007) methodology.…”
Section: Resultsmentioning
confidence: 99%
“…Since the inception of the COVID-19 pandemic, the majority of the literature on epidemiological modelling and public-health messages alike have scrutinized different nonpharmaceutical interventions in relation with their impact on R, the effective reproduction number [24,67]. For the latter more realistic scenarios (i.e.…”
Section: Metrics Under Considerationmentioning
confidence: 99%